IFN-? Induction of Apolipoprotein A-I Expression is Mediated by NF-?B Signalling in HepG2 Cells - Lui Siang Tong; Hong Kin Wong; Choy Hoong Chew (Tropical Life Sciences Research, 2019)
Liver inflammation is associated with changes in lipoprotein and apolipoprotein expression. Interferon-? (IFN-?), the sole representative of type II IFN, plays a pivotal role in modulating and intensifying inflammatory responses. This study was designed to identify the effect of IFN-? on apolipoproteinA-I (APOA-I) and to identify the involvement of nuclear factor–kappa B (NF-?B) in its regulation. Quantitative reverse transcription-polymerase chain reaction (qRT-PCR) and western blot analysis were performed to quantify the APOA-I expression in treated HepG2 cells. Here, we show that 50 ng/mL of IFN-? induced APOA-I mRNA and protein expression. Pretreatment of cells with NF-?B signalling pathway inhibitors, however, decreased the APOA-I expression levels. This study also demonstrated the direct involvement of NF-?B signalling in IFN-?-induced APOA-I expression, whereby IFN-? induced the levels of phosphorylated NF-?B p65 Ser468 and Ser536 expression to 2.59-fold and 1.63-fold, respectively. However, pretreatment of cells with NF-?B signalling pathway inhibitors attenuated their increment and subsequently reduced APOA-I expression in HepG2 cells. In summary, the present study successfully confirmed the role of NF-?B signalling and activation of p65 Ser468 and Ser536 in mediating IFN-? induction of APOA-I expression in HepG2 cells. Keradangan hati berkait rapat dengan perubahan dalam ekspresi lipoprotein dan apolipoprotein. Interferon-? (IFN-?), wakil tunggal jenis kedua IFN, memainkan peranan yang penting dalam memodulasi dan mempergiatkan tindak balas keradangan. Justeru itu, kajian ini direka untuk mengenal pasti kesan IFN-? terhadap apolipoprotein A-I (APOA-I) dan penglibatan nuclear factor–kappa B (NF-?B) dalam laluan isyarat tersebut. Tindak balas rantai polymerase transkripsi berbalik kuantitatif (qRT-PCR) dan analisis blot western telah dilaksanakan untuk menguantifikasi ekspresi APOA-I dalam sel-sel HepG2 selepas dirawat dengan IFN-?. Kajian ini menunjukkan bahawa 50 ng/mL IFN-? merangsangkan ekspresi mRNA dan protein APOA-I. Walau bagaimanapun, pra-rawatan sel dengan inhibitor laluan isyarat NF-?B mengurangkan tahap ekspresi APOA-I. Kajian ini juga mendemonstrasikan penglibatan langsung isyarat NF-?B dalam ekspresi APOA-I akibat rangsangan IFN-?, di mana IFN-? meningkatkan tahap fosforilasi NF-?B p65 Ser468 dan Ser536 kepada 2.59-ganda and 1.63-ganda. Namun demikian, pra-rawatan sel dengan perencat laluan isyarat NF-?B melumpuhkan peningkatkan tersebut dan kemudian mengurangkan ekspresi APOA-I dalam sel HepG2. Sebagai rumusan, kajian ini berjaya mengenalpasti peranan isyarat NF-?B dan pengaktifan p65 Ser468 dan Ser536 sebagai pengantara IFN-? ke atas induksi APOA-I di dalam sel-sel HepG2.